Desain Ruang Spasial Anak Berdasarkan Bentuk, Warna dan Tekstur : Anak Usia Dini - Yuzni, Siti Zulfa; Zulfikar, Ahmad; Rani, Cut Meuthia; Barlian, Edo (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Children's spatial space is an interaction space for playing and learning which can influence children's knowledge, social and emotional development. Aspects that must be considered in designing children's spatial spaces are safety, flexibility, sensory stimulus, social connectedness, accessibility and learning. In playing, children are free to move to develop their creativity and imagination in developing their knowledge. Children can get to know their space through exploration, interaction and direct experience with the process of recognizing shapes, colors and textures. Children's perceptions of space can shape their patterns and behavior in recognizing space through the process of seeing, observing and exploring space with their imagination and knowledge. The problem that can be developed is how children can recognize their space through the process of recognizing shapes, colors and textures. The goal to be achieved is the formation of children's spatial space through the application of learning room design oriented to shape, color and texture with play and learning methods. Observations were made on children's play activities in utilizing space and then analyzed to determine the space patterns that children needed. Observation results show that children can recognize space by recognizing the shapes, colors and textures found in space. Children's ability to recognize shapes, colors and textures can improve children's imagination and motor skills, literacy skills and emotional control.